Pengembangan Jiwa Kewirausahaan Anak Panti Asuhan Yatim Putri Aisyiyah Surakarta melalui Produksi dan Pemasaran Online Makanan Olahan - Suwandi, Joko; Jatmika, Surya; Chamsudin, Ahmad; Martama, Happy (Universitas Negeri Semarang, 2024)
The Yatim Putri Aisyiyah Orphanage Branch in West City strives to provide the children in the orphanage with the knowledge and life skills necessary for independent and morally upright living in the future. This preparation serves as a means for the orphanage children to have a bright future and be beneficial to others. Entrepreneurship is one of the life skills developed by the orphanage to foster interest, creativity, and innovation for future independent living. There are several types of simple processed food products that can be made by the girls in the orphanage, such as bangsren, galantin, dim sum, risoles, sausages, croquettes, cilok, and so on. The vacuum frozen model is chosen as the packaging for the products, ensuring that they can be stored for a long time, easily carried, and marketed through digital-based social media. The method of implementing community service is done by combining counseling, training, practice, and mentoring. The results of community service activities are as follows: (1) The Yatim Putri Aisyiyah children have gained knowledge about entrepreneurship and insight into independent living without relying on others. (2) The Yatim Putri Aisyiyah children have mastered productive life skills in the production and marketing of light processed products using social media as preparation for their future after leaving the orphanage.